Pel reconstruction on FPGA-augmented TriMedia. - Sima, M. (IEEE Transactions on VLSI systems)
This paper presents a TriMedia processor extended with three reconfigurable designs for entropy decoding (ED), inverse quantization (IQ), and two-dimensional (2-D) inverse discrete cosine transform (IDCT), and assesses the performance gain that is provided by such extensions when performing MPEG2-compliant pel reconstruction. We first describe an extension of the TriMedia architecture, which consists of a multiple-context field programmable gate array (FPGA)-based reconfigurable functional unit (RFU), a configuration unit managing the reconfiguration of the RFU, and their associated instructions. Then, we address the computation of the ED, IQ, and 2-D IDCT tasks, and propose to provide reconfigurable hardware support for a variable-length decoder that can decode two symbols per call (VLD-2), an inverse quantizer that can dequantize four coefficients per call (IQ-4), and an 1-D IDCT (1-D IDCT). The most important aspects concerning the implementation of the FPGA-mapped VLD-2, IQ-4, and 1-D IDCT units, as well as the organization of the software routines calling these FPGA-mapped computing units are outlined. Experimental results indicate that by configuring each of the VLD-2, IQ-4, and 1-D IDCT units on a different FPGA context, and by activating the contexts as needed, the FPGA-augmented TriMedia can perform MPEG2-compliant pel reconstruction with an average speed-up of 1.4× over the standard TriMedia.